The individual style development peculiarities for the elderly age group women - Дихнич, Л. П.; Харченко, А. В. (Art and Design, 2021)
The aim of the article is to study trends in clothing design for women of elder age group, to present the results of practical application of the styles synthesis in the individual image design. The integrated approach that combines sociological, psychological, art research methods have been used in the article. Method of interview, analytical, comparative, design-graphic, image-stylistic, image-associative methods have been applied. Women`s age groups determination approaches in the scientific literature have been analysed; the importance of aesthetic and psychological cues in the development of individual style for elder women is examined; the basic stylistic decisions on the example of the studied age group female images have been offered. The scientific novelty is in the determination of relationship between the aesthetic and psychological aspects and women`s clothing modern styles structure adaptation to the female consumer audience over the age of 45 needs. Practical significance is in the application of styles synthesis methods in the individual images development for different purposes for the studied age category. The obtained results can be used in the practical activities of stylists and fashion designers, in teaching practice in "Design" course.